Treatment of asymptomatic blunt cerebrovascular injury (BCVI): a systematic review. Issue 1 (26th April 2021) - Murphy, Patrick B; Severance, Sarah; Holler, Emma; Menard, Laura; Savage, Stephanie; Zarzaur, Ben L
Abstract : Background: The management of asymptomatic blunt cerebrovascular injury (BCVI) with respect to stroke prevention and vessel healing is challenging. Objectives: The aim of this systematic review was to determine if a specific treatment results in lower stroke rates and/or improved vessel healing in asymptomatic BCVI. Data sources: An electronic literature search of MEDLINE, EMBASE, Cochrane Library, CINAHL, SCOPUS, Web of Science, and ClinicalTrials.gov performed from inception to March 2020. Study eligibility criteria: Studies were included if they reported on a comparison of any treatment for BCVI and stroke and/or vessel healing rates. Participants and interventions: Adult patients diagnosed with asymptomatic BCVI(s) who were treated with any preventive medication or procedure. Study appraisal and synthesis methods: All studies were systematically reviewed and bias was evaluated by the Newcastle-Ottawa Scale. No meta-analysis was performed secondary to significant heterogeneity across studies in patient population, screening protocols, and treatment selection. The main outcomes were stroke and healing rate. Results: Of 8781 studies reviewed, 19 reported on treatment effects for asymptomatic BCVI and were included for review. Any choice of medical management was better than no treatment, but no specific differences between choice of medical management and stroke outcomes were found. Vessel healing was rare and the majority of healed vessels were following low-grade injuries. Limitations: Majority of the included studies were retrospective and at high risk of bias. Conclusions or implications of key findings: Asymptomatic BCVI should be treated medically using a consistent, local protocol. High-quality studies on the effect of individual antithrombotic agents on stroke rates and vessel healing for asymptomatic BCVI are required.